Becoming the hacker the playbook for getting inside the mind of an attacker - Pruteanu, Adrian (Expert insight., 2019)
Adrian Pruteanu adopts the mindset of both a defender and an attacker in this practical guide to web application testing. By giving key insights into attack vectors and defenses, Becoming the Hacker builds your ability to analyze from both viewpoints and create robust defense strategies.